Salt Tolerance in some Tree Species at Seedling Stage - Gupta, G. N.; Prasad, K. G.; Mohan, S.; Manivachakam, P. (Indian Forester, 1986)
In a pot culture study varying levels of salinity were Simulated in clay, loam and sand textured soils. Based on plant survival, height, leaf weight, stem weight total plant weight, root length and root/shoot ratio, it was concluded that Acacia nilotica and Eucalyptus camaldulensis could be grown with less than 50% growth reduction upto 5 ds/m salinity. Acacia nilotica withstood salinity of as high as 15 dS/m. Casuarina equisetifolia was moderate in salt tolerance. Ceiba pentandra and Acacia auriculaeformes were highly sensitive tree species and did not survive beyond 2.5 ds/m.